Knockdown of PHLDA2 promotes apoptosis and autophagy of glioma cells through the AKT/mTOR pathway. (3rd July 2022) - Guo, Chengyong; Liu, Shuo; Zhang, Tao; Yang, Jipeng; Liang, Zhaohui; Lu, Shengkui
Abstract: Pleckstrin homology like domain family A member 2 (PHLDA2) is an imprinted gene expressed in placenta and has been shown to be associated with tumor progression. However, the effect of PHLDA2 on glioma cell growth has not been reported yet. Data based on TCGA database showed that PHLDA2 was up-regulated in glioma tissues. Moreover, PHLDA2 was also elevated in glioma cells. Functional assays showed that siRNA-mediated knockdown of PHLDA2 reduced cell viability of glioma cells and suppressed the cell proliferation. Cell apoptosis of glioma cells was promoted by silencing of PHLDA2 with increased Bax and decreased Bcl-2. Silencing of PHLDA2 reduced protein expression of p62, enhanced LC3 and Beclin1 to promote autophagy. Phosphorylated AKT and mTOR were down-regulated in glioma cells by interference of PHLDA2. In conclusion, downregulation of PHLDA2 inhibited glioma cell proliferation, and promoted cell apoptosis and autophagy through inactivation of AKT/mTOR signaling.